Thrombomodulin is a stronger indicator of combined oral contraceptives-induced activated protein C pathway resistance in the thrombin generation test than activated protein C - Ninivaggi, Marisa; Sokolova, Lily; Donkervoort, Demy; de Laat, Bas; de Laat-Kremers, Romy (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe mechanism by which combined oral contraceptives (COCs) lead to hypercoagulation is not fully understood, although activated protein C (APC) pathway resistance has been implicated. APC and thrombomodulin (TM) tend to be considered as interchangeable reagents, even though their biological action in coagulation is different. However, it remains unclear which reagent is better suited for the detection of APC pathway resistance. We compared the effectiveness of TM and APC in TG to detect COC-induced APC pathway resistance using thrombin generation (TG).MethodsTG was measured on ST Genesia in 48 healthy women, of whom 24 used COCs. TG was triggered with STG-ThromboScreen (with and without TM), spiked with a low and high concentration of TM or APC (2 or 15 nM TM, or 1.5 or 5.5 nM APC), aimed to achieve 50% and 90% ETP inhibition, respectively.ResultsTG was higher in women using COCs. TM and APC inhibit TG in all women, although their inhibitory effect is more pronounced in women without COC compared to women with COC. The addition of 2 nM TM causes an ETP reduction of 40% (1,289 vs. 768 nM•min) in women without COC and an ETP reduction of 24% (1,704 vs. 1,287 nM•min) in women with COC. The addition of 1.5 nM APC causes an ETP reduction of 41% (1,289 vs. 759 nM•min) in women without COC and an ETP reduction of 23% (1,704 vs. 1,316 nM•min) in women with COC. The difference in effect between women with and without COC is largest when 15 nM TM, aimed at 90% ETP inhibition, is used. 15 nM TM leads to the smallest overlap in ETP inhibition between women with and without COC (27% overlap), compared to 2 nM TM (41% overlap), and 1.5 nM APC (38% overlap) and 5.5 nM APC (41% overlap).ConclusionAlthough TM and APC are often used interchangeably to assess the sensitivity of the APC system in TG, our findings suggest that TM is a better discriminator to detect COC-use induced APC pathway resistance. In addition, we found that the ETP is a better TG test readout for APC pathway resistance testing than the peak height.